Bank funding diversity, risk and profitability: Evidence from Vietnam in the context of the Covid-19 pandemic - Manh Hung Pham; Nhat Minh Nguyen (Cogent Business & Management, 2023)
This study empirically explores the effects of bank funding diversity on Vietnamese commercial banks' profitability and risk in the context of the COVID-19 pandemic. The panel regression method was used to analyze quarterly data from 27 Vietnamese commercial banks from Q1-2016 to Q1-2021. The study findings demonstrate that commercial banks with diverse financing sources are more profitable and riskier. In the meanwhile, the COVID-19 outbreak did not diminish the short-term profitability of Vietnamese commercial banks, but it did increase their exposure to risk. On the basis of the empirical findings, this paper also proposes a number of strategies to assist Vietnamese commercial banks in operating more effectively and securely in the context of the COVID-19 pandemic.
Keywords: 650; COVID-19; risk; Banks; panel data; Vietnam; profitability; funding diversity